Innovations in Urologic Surgical Training - Ma, Runzhuo (Curr Urol Rep, 2021)
PURPOSE OF THE REVIEW: This review aims to summarize innovations in urologic surgical training in the past five years. RECENT FINDINGS: Many assessment tools have been developed to objectively evaluate surgical skills and provide structured feedback to urologic trainees. A variety of simulation modalities (i.e., virtual/augmented reality, dry-lab, animal, and cadaver) have been utilized to facilitate the acquisition of surgical skills outside the high-stakes operating room environment. Three-dimensional printing has been used to create high-fidelity, immersive dry-lab models at a reasonable cost. Non-technical skills such as teamwork and decision-making have gained more attention. Structured surgical video review has been shown to improve surgical skills not only for trainees, but also for qualified surgeons. SUMMARY: Research and development in urologic surgical training has been active in the past five years. Despite these advances, there is still an unfulfilled need for a standardized surgical training program covering both technical and non-technical skills.